Late-Stage Two-Step C11–H Arylation of Dibenzooxa/thiazepines - Chen, Yang; Ma, Meng-Yao; Du, Hongguang; Xu, Jiaxi; Yang, Zhanhui (Synthesis, 2023)
A practical and efficient synthesis of 11-aryldibenzooxa/thiazepines is achieved, via a late-stage and two-step C11–H arylation of simple dibenzooxa/thiazepines. The adoption of Grignard addition and DDQ dehydrogenation allows for operationally simple and chemically reliable, step-efficient, and high-yielding transformations. The two-step and one-pot procedures provide excellent yields. The gram-scale experiment demonstrates the promising synthetic potentials in large-scale applications, and the advantages of this method are also highlighted in the efficient synthesis of an H460TaxR inhibitor.
Keywords: arylation; Grignard reaction; dehydrogenation; heterocycle; fused-ring systems